The distribution of financial wealth in the UK: Evidence from 2000 BHPS data - James Banks; Zoë Smith; Matt Wakefield (Institute for Fiscal Studies (IFS), 2002)
This paper examines evidence from the British Household Panel Study on the distribution of financial wealth amongst benefit units in 2000. It also provides some analysis of the links between financial wealth, pensions and housing wealth. For part of the sample, the data also allow a comparison of holdings in some elements of the financial portfolio in 2000, and in 1995. This paper examines evidence from the British Household Panel Study on the distribution of financial wealth amongst benefit units in 2000. Updated version with revised housing wealth estimates (tables V.5-V.7, A9-A12 and figure IV.4 affected)
Keywords: 330; Vermögensverteilung; Großbritannien